MORPHOLOGICAL STUDY OF PULMONARY FISSURES AND THEIR ANATOMICAL VARIATIONS IN ADULT CADAVERIC LUNGS (Asian Journal of Medical Research and Health Sciences, 2026)
Background and Rationale: Pulmonary fissures divide the lungs into anatomically and functionally distinct lobes, facilitating uniform expansion and serving as landmarks for bronchopulmonary segmentation. Variations in fissural morphology—such as incomplete, absent, or accessory fissures—may influence radiological interpretation and surgical outcomes. The present study was undertaken to document the morphological variations of pulmonary fissures in adult cadaveric lungs and compare them with classical anatomical descriptions. Methods: A total of 72 adult human cadaveric lungs (36 right and 36 left) were examined grossly in the Department of Anatomy. Each specimen was assessed for the presence, completeness, and absence of oblique and horizontal fissures, as well as accessory fissures. Fissural completeness was graded according to the Craig and Walker classification, and findings were compared with standard anatomical references and previous studies. Results: In the right lungs, the horizontal fissure was complete in 61.11%, incomplete in 27.78%, and absent in 11.11% of specimens; the oblique fissure was complete in 77.78% and incomplete in 22.22%. In the left lungs, the oblique fissure was complete in 75% and incomplete in 25%. Accessory fissures were rare, with an inferior accessory fissure observed in 2.78% of specimens. Grade I fissures predominated in both lungs, indicating a higher incidence of complete fissures. Discussion: The study confirms that variations in pulmonary fissures are common, particularly involving the right horizontal fissure. Incomplete fissures may result from partial fusion of lobes during embryogenesis and can complicate lobectomy or segmentectomy procedures. The rarity of accessory fissures aligns with previous Indian cadaveric studies, though regional differences may exist. Conclusion: Incomplete fissures are frequent anatomical variants, while accessory fissures are uncommon. Recognition of these variations is essential for anatomists, radiologists, and thoracic surgeons to avoid diagnostic errors and operative complications. Further studies incorporating radiological correlation are recommended to elucidate population based differences and clinical implications.